P639 Epidemiology and patient burden of rectovaginal and anovaginal fistulas in patients with Crohn's disease: A systematic review. (27th May 2021) - Iglay, K; Bennett, D; Kappelman, M; Thai, S; Aldridge, M; Karki, C; Cook, S
Abstract: Background: Rectovaginal fistulas (RVF) and anovaginal fistulas (AVF) in Crohn's disease (CD) are rare, debilitating conditions that present substantial disease and treatment burdens for women. In this systematic literature review (SLR), articles relating to the epidemiology and burden of CD-related RVF and AVF were assessed in order to summarize evidence from observational studies and highlight knowledge gaps. Methods: Articles published in the past 10 years in PubMed and Embase that provide data on incidence, prevalence and insight into the patient experience and disease burden of CD-related RVF and AVF (PROSPERO registration number CRD42020177732) were identified. Two trained reviewers used pre-specified eligibility criteria to identify studies for inclusion and evaluate risk of bias using the Risk Of Bias In Non-randomized Studies of Interventions (ROBINS-I) tool for observational studies. Data were extracted for a range of variables, including study type and design, population, outcomes and limitations. Results: Of the 582 records identified, 316 full-text articles were assessed, and 16 studies that met a priori eligibility criteria were included (Figure). Three epidemiology studies were identified, with one study estimating the prevalence of RVF to be 2.3% in women with CD. No studies relating to the incidence or prevalence of AVF were identified. Seven of 12 treatment-pattern studies reported that patients had or required additional procedures before and/or after the intervention of interest, demonstrating substantial treatment burden. Of the nine studies that reported healing/success across multiple surgical types, rates ranged from 14.4% to 81.0%. In the seven studies that assessed clinical outcomes, healing rates were in the range 50–75%, with varying estimates dependent on population and intervention. Two studies reported recurrence rates of 13.3–55.8% across multiple surgical interventions. Patient-reported outcomes obtained using standardized measures were reported in only one of the 16 studies and were limited to overall health related quality of life, faecal incontinence-related quality of life and female sexual function index. None of the 16 studies included reported healthcare-resource utilization in this patient population. Conclusion: This SLR shows the high disease and treatment burdens of RVF and AVF in patients with CD and identifies multiple evidence gaps in this field. The published literature lacks robust, generalizable data and demonstrates a compelling need for substantial novel research into these rare and debilitating sequelae of CD. Sponsor: Takeda Pharmaceuticals USA, Inc.